HUBUNGAN RIWAYAT PEMBERIAN ASI EKSLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI KABUPATEN TIMOR TENGAH SELATAN - Nur Asyah; Dina M.S Henukh; Jusuf Amnifu (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
Introduction: Stunting describes a serious problem that occurs in toddlers caused by chronic malnutrition. Toddlers who experience stunting are caused by a lack of good nutrition in the child's body and at the maximum one of the factors is exclusive breastfeeding as a baby. The purpose of this study was to analyze the relationship between exclusive breastfeeding and the incidence of stunting in children under five in Timor Tengah Selatan Regency. Methods: This study used a case-control research design with a retrospective approach. The population is all children under five with stunting and not stunting in South Central Timor district, with a research subject of 200 samples consisting of 100 cases and 100 control respondents, the sampling technique was purposive sampling. The independent variable is a history of exclusive breastfeeding while the dependent variable is the incidence of stunting. The data collection tool is a questionnaire sheet. Analysis using univariate and bivariate with Chi-Square test. Result: Chi-Square test obtained Asymp Sig (2-tailed) 0.000 <α (0.05) so that H0 is rejected and H1 is accepted. Conclusion: There is a relationship between a history of exclusive breastfeeding and the incidence of stunting.